2008
DOI: 10.1111/j.1365-3016.2008.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal polychlorinated biphenyl exposures in eastern Slovakia modify effects of social factors on birthweight

Abstract: Polychlorinated biphenyls (PCB) were widely used for industrial purposes and consumer products, but because of their toxicity, production was banned by most industrialised countries in the late 1970s. In eastern Slovakia, they were produced until 1985. During 2002-04, a birth cohort of mothers (n = 1057) residing in two Slovak districts was enrolled at delivery, and their specimens and information were collected after birth. Congeners of PCBs were measured in maternal serum by high-resolution gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 55 publications
8
68
2
1
Order By: Relevance
“…There were few results reported gender difference, they frequently indicated a stronger negative effect on the birth weight among male infants (Rylander et al, 1996;Baibergenova et al, 2003;Sonneborn et al, 2008;Hertz-Picciotto et al, 2005;Vartiainen et al, 1998). Previous reports have indicated that increased maternal serum PCBs levels are associated with reduced birth weight in male infants and have suggested a greater susceptibility of male conceptuses, either in the fetal or embryonic period (Sonneborn et al, 2008;Hertz-Picciotto et al, 2005). Some of the studies reporting gender difference in the PCBs effects did not actually measure PCBs levels, but used a surrogate for exposure such as estimated fish consumption (Rylander et al, 1996) or residential information (Baibergenova et al, 2003), which may entail greater errors in exposure classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were few results reported gender difference, they frequently indicated a stronger negative effect on the birth weight among male infants (Rylander et al, 1996;Baibergenova et al, 2003;Sonneborn et al, 2008;Hertz-Picciotto et al, 2005;Vartiainen et al, 1998). Previous reports have indicated that increased maternal serum PCBs levels are associated with reduced birth weight in male infants and have suggested a greater susceptibility of male conceptuses, either in the fetal or embryonic period (Sonneborn et al, 2008;Hertz-Picciotto et al, 2005). Some of the studies reporting gender difference in the PCBs effects did not actually measure PCBs levels, but used a surrogate for exposure such as estimated fish consumption (Rylander et al, 1996) or residential information (Baibergenova et al, 2003), which may entail greater errors in exposure classification.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of lower-level PCBs exposure during pregnancy observed associations with decreased birth weight and other growth parameters (Fein et al, 1984;Rylander et al, 1996: Rylander et al, 1998Patandin et al, 1998;Karmaus and Zhu, 2004;Hertz-Picciotto et al, 2005;Sagiv et al, 2007;Sonneborn et al, 2008). In the Lake Michigan fish consumer study, cord serum PCBs levels predicted LBW and smaller birth head circumference (Fein et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant and nursing women may pass the dioxins and/or PCBs to their newborns via transplacental transfer and by breastfeeding mothers (Suzuki et al 2005, Wang et al 2004. Several studies on exposure to lower levels of dioxins or PCBs during pregnancy have shown a relationship with low birth weight and other growth parameters (HertzPicciotto et al 2005, Patandin et al 1998, Sonneborn et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…These studies mainly originate in the northern and western parts of Europe with only studies published in the Czech and Slovak Republics of the Danube area (11)(12)(13). Globally much attention is toward birth cohorts …”
Section: Introductionmentioning
confidence: 99%